Host matrix impact on Er3+ upconversion emission and its temperature dependence1. Issue 21 (6th March 2015) - Singh, A. K.; Shahi, Praveen Kumar; Rai, S. B.; Ullrich, Bruno
<x xml:space="preserve">Abstract</x> Impact of phonon frequency and crystal structure of the host lattice on upconversion emission.